Membangun Desa Sendang Sebagai Desa Berkelanjutan Berbasis Penguatan Moderasi Beragam Dan Kearifan Lokal - Cahyani, Seftiana Dwi; Solichin, Moh. Badrus; Auliya, Safira Rizki; A, Rama Dona Risqi; Nida, Karima Naufalin; Salam, M Alfa; M, M. Wildan; Rizal, Achmad; Fadhilah, Hery; A, Rohmatus Zakkiyah K; P , Rizky Tiara; Dewi, Ikvina Kurnia; Ardila, Nourma Nur; Janah, Amma Huqot Nur; Adelya, Nandita; Cholifah, Siti Nur (Welfare : Jurnal Pengabdian Masyarakat, 2023)
The implementation of Real Work Lectures (KKN) in Sendang Village aims to support the KKN theme that has been established by the campus, namely "Building a Sustainable Village Based on Strengthening Religious Moderation and Local Wisdom". Apart from that, students are expected to be able to share the knowledge gained during lectures, participate actively, and have a sense of concern for various problems faced by society in the field. It is hoped that this KKN activity can increase mutually beneficial collaboration between students, the community, and the village government. The method used in this service is community participation and empowerment through student participation in community activities. The results of this service activity include increasing community awareness and participation in strengthening religious moderation and applying local wisdom for sustainable village development. Apart from that, the creation of positive synergy between students, the community, and the village government also contributes to achieving better development goals for Sendang Village. This KKN activity is a real step in realizing sustainable development based on religious values and local wisdom.